Tuberculosis in the 1990s: From Bedside to Bench and Back - Frances B Jamieson; Pamela Chedore (Canadian Respiratory Journal)
Since the mid-1980s, the rate of new cases of tuberculosis (TB) diagnosed in Canada ceased to follow a downward trend, and has instead stabilized at approximately 7 cases/100,000 population. In the United States, a similar trend emerged, such that in the early 1990s there was an increase in new cases of TB. Outbreaks of drug-resistant TB also occurred with devastating clinical impact. These observations prompted laboratories to re-examine their role in halting the spread of TB. Laboratories play a critical part in the diagnosis of TB; procedures must be optimized to provide rapid and accurate results. This review discusses the role of the mycobacteriology laboratory in the diagnosis of TB, and how new technologies available today have enhanced the ability of the laboratory to provide timely, efficient and accurate results.